The Formation and Use of Tourist Potential of Regions in the Context of Socio-Economic Development - Vladimir Alexandrovich Shamakhov; Alexey Dmitriyevich Shmatko (Управленческое консультирование, 2018)
The article studies the issues of formation and use of tourist potential of regions in the context of socio-economic development on the basis of the results obtained in the monograph «Management of socio-economic development and tourism and recreational activities at the Federal, regional and local levels: a typological approach». Contained in the article the author’s approach is considered on a concrete example - the municipal formation Ivangorod of Kingisepp municipal district of Leningrad region. Approbation of results was carried out in the framework of qualification for persons holding public office of the Leningrad region and the public civil servants of the Leningrad region, replacing posts of civil service in Executive authorities of the Leningrad region «An effective system of regional management as a factor ensuring international competitiveness of Russia».